Genipin diffusion and reaction into a gelatin matrix for tissue engineering applications. Issue 3 (5th November 2015) - Montemurro, Francesca; De Maria, Carmelo; Orsi, Gianni; Ghezzi, Lisa; Tinè, Maria Rosaria; Vozzi, Giovanni
Abstract: Genipin is a natural low‐toxic cross‐linker for molecules with primary amino groups, and its use with collagen and gelatin has shown a great potential in tissue engineering applications. The fabrication of scaffolds with a well‐organized micro and macro topology using additive manufacturing systems requires an accurate control of working parameters, such as reaction rate, gelling time, and diffusion constant. A polymeric system of 5% w/v gelatin in PBS with 2 mg/mL collagen solutions in a 1:1 weight ratio was used as template to perform measurements varying genipin concentration in a range of 0.1–1.5% w/w with respect to gelatin. In the first part of this work, the reaction rate of the polymeric system was estimated using a new colorimetric analysis of the reaction. Then its workability time, closely related to the gelling time, was evaluated thanks to rheological analysis: finally, the quantification of static and dynamic diffusion constants of genipin across nonreacting and reacting membranes, made respectively by agarose and gelatin, was performed. It was shown that the colorimetric analysis is a good indicator of the reaction progress. The gelling time depends on the genipin concentration, but a workability window of 40 min guaranteed up to 0.5% w/w genipin. The dynamic diffusion constant of genipin in the proposed polymeric system is in the order of magnitude of 10 −7 . The obtained results indicated the possibility to use the genipin, gelatin, and collagen, in the proposed concentrations, to build well‐defined hydrogel scaffolds with both extrusion‐based and 3D ink‐jet system. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 473–480, 2017.